Объяснение:
|x²-1|+|x²-9|=x+18
Находим нули подмодульных выражений:
x²-1=0 (x+1)*(x-1)=0 x₁=-1 x₂=1.
x²-9=0 (x+3)*(x-3)=0 x₃=-3 x₄=3. ⇒
-∞-3-113+∞
1) x∈(-∞;-3)
x²-1+x²-9=x+18
2x^2-x-28=0
D=225 √D=15
x₁=-3,5 ∈ x₂=4∉.
2) x∈[-3;-1].
x²-1+(-(x²-9))=x+18
x²-1-x²+9=x+18
8=x+18
x=-10 ∉.
3) x∈(-1;1)
-(x^2-1)+(-(x^2-9))=x+18
-x²+1-x²+9=x+18
-2x²+10-x-18=0
2x²+x+8=0
D=-63 ⇒ Уравнение не имеет действительных корней.
4) x∈[1;3].
x²-1+(-(x²-9))=x-18
x-1-x^2+9=x+18
x=-10 ∉,
5) x∈(3;+∞)
x²-1+x²-9=x+18
2x²-10=x+18
2x^2-x-28=0
D=225 √D=15
x₁=-3,5 ∉ x₂=4 ∈.
ответ: x₁=-3,5 x₂=4.
3x - 3 + 2x + 4 < 4x + 4
5x + 1 < 4x + 4
5x - 4x < 4 - 1
x < 3